Preparation method of composite coating and composite coating

By forming a composite coating on the surface of the titanium alloy, the problem of insufficient wear resistance and corrosion resistance of titanium alloy components is solved, and the wear resistance performance of titanium alloy is improved, and its service life and reliability are extended.

CN119243287AActive Publication Date: 2025-01-03XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411770160.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-03
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

During service, titanium alloy components have problems such as insufficient wear resistance, galvanic corrosion resistance and thermal salt corrosion resistance, which leads to a decrease in reliability and service life, affecting the operation safety of equipment.

Method used

The preparation method of composite coating is adopted, including uniformly dispersing the activated MoS2 nano powder in the electrolyte, performing microarc oxidation treatment to form a TiO2/MoS2 layer, and then processing it in the sealing liquid to form a TiO2 corrosion-resistant layer. Finally, a Ti/MoS2 layer was formed by vapor deposition under a vacuum argon atmosphere to form a composite coating that was resistant to wear.

Benefits of technology

It significantly improves the friction-reduction and wear resistance and corrosion resistance of titanium alloy, effectively overcomes the hot salt corrosion problem of titanium alloy in high-temperature salt-containing environment, and extends the service life and reliability of titanium alloy components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243287A_ABST
    Figure CN119243287A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a composite coating and the composite coating, and relates to the technical field of metal coatings, the method comprises the following steps: 1, uniformly dispersing activated MoS2 nano-powder in an electrolyte to obtain a composite electrolyte; secondly, a titanium alloy matrix is placed in the composite electrolyte to be subjected to micro-arc oxidation treatment, so that a micro-arc oxidation layer with TiO2 / MoS2 is generated on the surface of the titanium alloy matrix; thirdly, the titanium alloy base body with the TiO2 / MoS2 micro-arc oxidation layer is immersed in hole sealing liquid, then drying treatment is conducted, and a base material with a hole sealing TiO2 corrosion-resistant layer is obtained; and 4, the base material with the hole-sealing TiO2 corrosion-resistant layer is placed in a vacuum chamber of vapor deposition equipment to serve as an anode, a MoS2 target material and a Ti target material serve as cathodes, coating treatment is conducted in the argon atmosphere with the vacuum degree being 1 Pa, and therefore the corrosion-resistant composite coating is formed on the surface of the base material with the hole-sealing TiO2 corrosion-resistant layer. The corrosion resistance of the composite coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present disclosure relate to the technical field of metal coatings, and in particular, to a method for preparing a composite coating and the composite coating. Background Art

[0002] Titanium alloy has the advantages of light weight, high strength, and high temperature resistance. It is an ideal material for major industrial equipment to develop towards large-scale, complex service environment, harsh component working conditions, and long-term service life requirements. It is widely used in aerospace, marine, nuclear energy, chemical and medical fields. However, in the process of actual application, titanium alloy components have problems of insufficient wear resistance, galvanic corrosion resistance and hot salt corrosion resistance during service, which easily leads to the reduction of reliability and service life of titanium alloy components during use, and even affects the operational safety of the entire equipment.

[0003] In order to solve this problem, surface strengthening can be used to improve the surface performance of titanium alloy components. At present, the research and development of titanium alloy surface coating materials mainly focuses on improving wear resistance; however, on the basis of wear resistance, how to reduce galvanic corrosion between titanium alloy and dissimilar materials and hot salt corrosion in high temperature salt environment has also become an urgent problem to be solved. Summary of the invention

[0004] The purpose of the present disclosure is to provide a method for preparing a composite coating and a composite coating, thereby at least to a certain extent overcoming the problem of how to reduce galvanic corrosion between titanium alloys and dissimilar materials and hot salt corrosion in a high-temperature saline environment due to the limitations and defects of the relevant technology.

[0005] According to one aspect of the present disclosure, there is provided a method for preparing a composite coating, comprising: Step 1: Evenly dispersing the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte; Step 2: placing the titanium alloy substrate in the composite electrolyte for micro-arc oxidation treatment to generate a micro-arc oxidation layer with TiO2 / MoS2 on the surface of the titanium alloy substrate; Step 3: immersing the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer into a sealing liquid, followed by drying to obtain a substrate with a sealed TiO2 corrosion-resistant layer; Step 4: Place the substrate with the sealed TiO2 corrosion-resistant layer in the vacuum chamber of the vapor deposition equipment as the anode, use the MoS2 target and the Ti target as the cathode, and perform coating treatment in an argon atmosphere with a vacuum degree of 1 Pa to form a wear-resistant composite coating on the surface of the substrate with the sealed TiO2 corrosion-resistant layer.

[0006] In an exemplary embodiment of the present disclosure, the activated MoS2 nanopowder used in the preparation process of the composite electrolyte is obtained in the following manner: 10-20g of MoS2 nanopowder is immersed in a mixture of 0.05-0.1g of sodium dodecyl sulfate and 200-300g of ethanol and stirred for 2h for activation treatment to obtain an activated mixed solution, and the activated mixed solution is dried and sieved to obtain activated MoS2 nanopowder.

[0007] In an exemplary embodiment of the present disclosure, the preparation process of the composite electrolyte is obtained by the following method: 1-5g / L activated MoS2 nanopowder, 10-15g / L sodium silicate, 0.5-1g / L sodium hypophosphite, 2-5g / L sodium tungstate, and 2-8ml / L glycerol are prepared into an electrolyte, continuously stirred for 1-2h, and ultrasonically vibrated for 0.5-1.5h to evenly distribute the activated MoS2 nanopowder in the electrolyte.

[0008] In an exemplary embodiment of the present disclosure, in the preparation process of the micro-arc oxidation layer with TiO2 / MoS2, the frequency used in the micro-arc oxidation treatment process is 400-800 Hz, the forward duty cycle is 5-30%, the negative duty cycle is 5%-30%, the forward voltage is 350-500V, the negative voltage is 10-50V, and the oxidation time is 20-40min.

[0009] In an exemplary embodiment of the present disclosure, the sealing liquid is prepared by the following method: 1) Mixing 0.5-1.5 g / L of silane coupling agent with 2-10 g / L of organic solvent to obtain a solvent mixing result; 2) Stirring the solvent mixture for 36-48 hours to activate the solvent mixture to obtain a solvent activation result; 3) Add 5-10 g / L potassium fluorozirconate, 1-3 g / L nano titanium dioxide and 1-5 g / L triethanolamine to the solvent activation result and ultrasonically vibrate for 0.5 h to obtain the sealing liquid.

[0010] In an exemplary embodiment of the present disclosure, the substrate with a sealed TiO2 corrosion-resistant layer is prepared in the following manner: a titanium alloy substrate with a TiO2 / MoS2 micro-arc oxidation layer is placed in a sealing liquid and immersed for 5-10 minutes, and the immersed titanium alloy substrate is placed in an oven and baked at 160°C for 15 minutes, and then the baking is repeated 3-5 times and then dried again for 30 minutes to obtain a substrate with a sealed TiO2 corrosion-resistant layer.

[0011] In an exemplary embodiment of the present disclosure, the composite coating is prepared in the following manner: 1) placing a substrate with a sealed TiO2 corrosion-resistant layer in a vacuum chamber of a vapor deposition device and maintaining the vacuum degree at 1 Pa; 2) turning on the MoS2 target, using an RF power supply as the power source, and setting the sputtering power of the RF power supply to 200-250W; 3) turning on the Ti target, using a DC power supply as the power source, setting the current of the DC power supply to 50-100A, setting the bias voltage to -200V~-400V, the duty cycle to 40%-60%, and the deposition time to 1-3h, so as to plate the composite coating on the surface of the substrate with the sealed TiO2 corrosion-resistant layer.

[0012] According to one aspect of the present disclosure, there is provided a composite coating obtained by the method for preparing a composite coating according to any one of the above-mentioned items, wherein the composite coating comprises a micro-arc oxidation TiO2 / MoS2 layer, a TiO2 sealing layer and a vapor deposited Ti / MoS2 layer.

[0013] In an exemplary embodiment of the present disclosure, the thickness of the micro-arc oxidation TiO2 / MoS2 layer is 10-15 μm; the thickness of the TiO2 sealing layer is 1-1.5 μm; and the thickness of the vapor deposited Ti / MoS2 layer is 1-3 μm.

[0014] In an exemplary embodiment of the present disclosure, the atomic percentage of Ti in the vapor deposited Ti / MoS2 layer is 2%-10%.

[0015] In the preparation method of the composite coating provided in the embodiment of the present disclosure, on the one hand, the MoS2 nanopowder after activation treatment is uniformly dispersed in the electrolyte to obtain a composite electrolyte; then the titanium alloy substrate is placed in the composite electrolyte for micro-arc oxidation treatment to generate a micro-arc oxidation layer with TiO2 / MoS2 on the surface of the titanium alloy substrate; then the titanium alloy substrate with the micro-arc oxidation layer of TiO2 / MoS2 is immersed in a sealing liquid, and then dried to obtain a substrate with a sealed TiO2 corrosion-resistant layer; finally, the substrate with the sealed TiO2 corrosion-resistant layer is placed In the vacuum chamber of the vapor deposition equipment, MoS2 target and Ti target are used as the anode, and the cathode is used. The coating treatment is carried out in an argon atmosphere with a vacuum degree of 1Pa to form a wear-resistant composite coating on the surface of the substrate with a sealed TiO2 corrosion-resistant layer; since a micro-arc oxidation layer with TiO2 / MoS2 can be generated on the surface of the titanium alloy substrate by micro-arc oxidation, the friction reduction and wear resistance of the titanium alloy can be improved; on the other hand, since a multi-step sealing method can be used to obtain a sealed TiO2 corrosion-resistant layer, the corrosion resistance of the composite coating is further improved.

[0016] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0018] Figure 1 A flow chart of a method for preparing a composite coating according to an exemplary embodiment of the present disclosure is schematically shown.

[0019] Figure 2 An example diagram of a composite coating obtained based on Example 2 according to an example embodiment of the present disclosure is schematically shown.

[0020] Figure 3 An example diagram of a micro-arc oxidation layer obtained based on Comparative Example 1 according to an example embodiment of the present disclosure is schematically shown.

[0021] Figure 4 A morphology diagram obtained after hot salt corrosion of a surface coating on a titanium alloy substrate according to an exemplary embodiment of the present disclosure is schematically shown.

[0022] Figure 5 A morphology diagram obtained after hot salt corrosion of a composite coating obtained based on Example 2 according to an exemplary embodiment of the present disclosure is schematically shown.

[0023] Figure 6 A morphology diagram obtained after hot salt etching of the surface of the micro-arc oxidation layer obtained in Comparative Example 1 according to an exemplary embodiment of the present disclosure is schematically shown. DETAILED DESCRIPTION

[0024] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.

[0025] The terms "a", "an", "the" and "said" used in this specification are used to indicate the presence of one or more elements / components, etc.; the terms "including" and "having" are used to express an open-ended inclusion and mean that there may be additional elements / components, etc. in addition to the listed elements / components, etc.; the terms "first" and "second" etc. are used only as labels and are not intended to limit the quantity of their objects.

[0026] In view of the problem that the galvanic corrosion between titanium alloy and dissimilar materials and hot salt corrosion in high temperature salty environment cannot be reduced in the related art, the exemplary embodiment of the present disclosure first provides a method for preparing a composite coating. Figure 1 As shown, the preparation method of the composite coating may include the following steps: Step S110, uniformly dispersing the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte; Step S120, placing the titanium alloy substrate in the composite electrolyte for micro-arc oxidation treatment to generate a micro-arc oxidation layer with TiO2 / MoS2 on the surface of the titanium alloy substrate; Step S130, immersing the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer into a sealing liquid, followed by drying to obtain a substrate with a sealed TiO2 corrosion-resistant layer; Step S140, placing the substrate with the sealed TiO2 corrosion-resistant layer in the vacuum chamber of the vapor deposition equipment as the anode, using MoS2 target and Ti target as the cathode, and performing coating treatment in an argon atmosphere with a vacuum degree of 1 Pa to form a wear-resistant composite coating on the surface of the substrate with the sealed TiO2 corrosion-resistant layer.

[0027] In the preparation method of the composite coating described above, on the one hand, the activated MoS2 nanopowder is uniformly dispersed in the electrolyte to obtain a composite electrolyte; then the titanium alloy substrate is placed in the composite electrolyte for micro-arc oxidation treatment to generate a micro-arc oxidation layer with TiO2 / MoS2 on the surface of the titanium alloy substrate; then the titanium alloy substrate with the micro-arc oxidation layer of TiO2 / MoS2 is immersed in a sealing liquid, followed by drying to obtain a substrate with a sealed TiO2 corrosion-resistant layer; finally, the substrate with the sealed TiO2 corrosion-resistant layer is placed in a gas phase The vacuum chamber of the deposition equipment is used as the anode, and the MoS2 target and Ti target are used as the cathode. The coating treatment is carried out in an argon atmosphere with a vacuum degree of 1Pa to form a wear-resistant composite coating on the surface of the substrate with a sealed TiO2 corrosion-resistant layer. Since a micro-arc oxidation layer with TiO2 / MoS2 can be generated on the surface of the titanium alloy substrate, the friction reduction and wear resistance of the titanium alloy can be improved. On the other hand, since a multi-step sealing method can be used to obtain a sealed TiO2 corrosion-resistant layer, the corrosion resistance of the composite coating is further improved.

[0028] It should be further explained here that in the preparation method of the composite coating provided above, in the process of actual application, first, a composite micro-arc oxidation layer is prepared in the first stage to improve the friction reduction and wear resistance of the composite coating; secondly, multi-step sealing is performed in the second stage to improve the corrosion resistance of the composite coating; in the third stage, a Ti / MoS2 composite coating is prepared by vapor deposition to further improve the friction reduction performance of the composite coating; finally, the composition and structure of the composite coating on the surface of the titanium alloy are optimally designed to effectively overcome the problems of insufficient wear resistance, galvanic corrosion resistance and hot salt corrosion resistance of the titanium alloy.

[0029] The following will explain and illustrate the various steps involved in the preparation method of the composite coating in detail. Specifically: In step S110, the activated MoS2 nanopowder is evenly dispersed in the electrolyte to obtain a composite electrolyte.

[0030] Specifically, the activated MoS2 nanopowder used in the preparation process of the composite electrolyte recorded herein is obtained by the following method: 10-20g of MoS2 nanopowder is immersed in a mixture of 0.05-0.1g of sodium dodecyl sulfate and 200-300g of ethanol and stirred for 2h for activation treatment to obtain an activated mixed solution, and the activated mixed solution is dried and sieved to obtain the activated MoS2 nanopowder. Further, under this premise, the preparation process of the composite electrolyte is obtained by the following method: 1-5g / L activated MoS2 nanopowder, 10-15g / L sodium silicate, 0.5-1g / L sodium hypophosphite, 2-5g / L sodium tungstate, 2-8ml / L glycerol are prepared into an electrolyte, continuously stirred for 1-2h, ultrasonically shaken for 0.5-1.5h, and the activated MoS2 nanopowder is evenly distributed in the electrolyte.

[0031] In step S120, the titanium alloy substrate is placed in the composite electrolyte for micro-arc oxidation treatment to generate a micro-arc oxidation layer with TiO2 / MoS2 on the surface of the titanium alloy substrate.

[0032] Specifically, in the preparation process of the micro-arc oxidation layer with TiO2 / MoS2, the frequency used in the micro-arc oxidation treatment process is 400-800Hz, the forward duty cycle is 5-30%, the negative duty cycle is 5%-30%, the forward voltage is 350-500V, the negative voltage is 10-50V, and the oxidation time is 20-40min.

[0033] In step S130, the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer is immersed in a sealing liquid, and then dried to obtain a substrate with a sealed TiO2 corrosion-resistant layer.

[0034] Specifically, the sealing liquid is prepared by the following method: 1) mixing 0.5-1.5 g / L of silane coupling agent with 2-10 g / L of organic solvent to obtain a solvent mixture; 2) stirring the solvent mixture for 36-48 hours to activate the solvent mixture to obtain a solvent activation result; 3) adding 5-10 g / L of potassium fluorozirconate, 1-3 g / L of nano titanium dioxide and 1-5 g / L of triethanolamine to the solvent activation result and ultrasonically shaking for 0.5 hours to obtain the sealing liquid. The silane coupling agent described here is KH507.

[0035] Under this premise, a substrate with a sealed TiO2 corrosion-resistant layer is prepared in the following manner: a titanium alloy substrate with a TiO2 / MoS2 micro-arc oxidation layer is immersed in a sealing liquid for 5-10 minutes, and the immersed titanium alloy substrate is placed in an oven and baked at 160°C for 15 minutes, and then the baking is repeated 3-5 times and then dried again for 30 minutes to obtain a substrate with a sealed TiO2 corrosion-resistant layer.

[0036] In step S140, the substrate with the sealed TiO2 corrosion-resistant layer is placed in the vacuum chamber of the vapor deposition equipment as an anode, and the MoS2 target and the Ti target are used as cathodes. The coating treatment is performed in an argon atmosphere with a vacuum degree of 1 Pa to form a wear-resistant composite coating on the surface of the substrate with the sealed TiO2 corrosion-resistant layer.

[0037] Specifically, the composite coating is prepared by the following method: 1) placing a substrate with a sealed TiO2 corrosion-resistant layer in a vacuum chamber of a vapor deposition device and maintaining the vacuum degree at 1 Pa; 2) turning on the MoS2 target, using a radio frequency power supply as the power source, and setting the sputtering power of the radio frequency power supply to 200-250W; 3) turning on the Ti target, using a direct current power supply as the power source, setting the current of the direct current power supply to 50-100A, setting the bias voltage to -200V~-400V, the duty cycle to 40%-60%, and the deposition time to 1-3h, so as to plate the composite coating on the surface of the substrate with the sealed TiO2 corrosion-resistant layer.

[0038] Furthermore, the composite coating obtained based on the preparation method of the composite coating described above may include a micro-arc oxidation TiO2 / MoS2 layer, a TiO2 sealing layer and a vapor deposited Ti / MoS2 layer; at the same time, the thickness of the micro-arc oxidation TiO2 / MoS2 layer is 10-15μm; the thickness of the TiO2 sealing layer is 1-1.5μm; the thickness of the vapor deposited Ti / MoS2 layer is 1-3μm; further, the atomic percentage of Ti in the vapor deposited Ti / MoS2 layer is 2%-10%; further, the composite coating obtained based on the exemplary embodiment of the present disclosure can be used for TA2, TC4, TC6, TC11, Ti5331 and other alloy grades.

[0039] At this point, the preparation method of the composite coating recorded in the exemplary embodiment of the present disclosure has been fully realized. Based on the above-mentioned contents, it can be known that the preparation method of the composite coating recorded in the exemplary embodiment of the present disclosure has at least the following advantages: on the one hand, the TC6 alloy is treated by micro-arc oxidation, and the activated MoS2 nanopowder is evenly dispersed in the electrolyte to obtain a TiO2 / MoS2 coating, which can greatly improve the friction reduction and wear resistance of the TC6 alloy; on the other hand, a multi-step sealing method is adopted to obtain a TiO2 corrosion-resistant layer, which further improves the corrosion resistance of the coating; finally, a physical vapor deposition method is used to prepare a MoS2 / Ti friction reduction layer; on the other hand, the exemplary embodiment of the present disclosure prepares a composite coating on the surface of the TC6 alloy by combining micro-arc oxidation with physical vapor deposition, adopts a typical multi-layer design, combines the advantages of different coating components, greatly improves its friction reduction and wear resistance and heat salt corrosion resistance, can meet the use requirements of a variety of complex working conditions, and has good applicability.

[0040] The following will further explain and illustrate the preparation method of the composite coating in conjunction with specific embodiments. Specifically: Embodiment 1: A method for preparing a composite coating and a composite coating, comprising the following steps: Step 1: Evenly disperse the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte.

[0041] Step 2: placing the clean titanium alloy substrate in the composite electrolyte of step 1 for micro-arc oxidation treatment to obtain a TiO2 / MoS2 micro-arc oxidation layer on the surface of the titanium alloy substrate.

[0042] Step three: immerse the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer in step two into a sealing liquid, and then dry it to obtain a substrate with a sealing TiO2 corrosion-resistant layer.

[0043] Step 4: Place the sample obtained in step 3 in the vacuum chamber of the vapor deposition equipment as the anode, use MoS2 target and Ti target as the cathode, and perform coating treatment in an argon atmosphere with a vacuum degree of 1 Pa to form a MoS2 / Ti layer on the surface to obtain a wear-resistant composite coating.

[0044] In step 1 of this embodiment, the activation method of MoS2 nanopowder is: immerse 10g MoS2 nanopowder in a mixed solution of 0.05g sodium dodecyl sulfate and 200g ethanol and stir for 2h for activation treatment, and then dry and sieve to obtain the activated MoS2 nanopowder.

[0045] Wherein, in the step one of this embodiment, the composite electrolyte preparation method is to prepare 1g / L activated MoS2 nanopowder, 10g / L sodium silicate, 0.5g / L sodium hypophosphite, 2g / L sodium tungstate, and 4ml / L glycerol into an electrolyte, continuously stirred for 1h, ultrasonically oscillated for 0.5h, and the activated MoS2 nanopowder is evenly distributed in the electrolyte. At the same time, in the step two of this embodiment, the TiO2 / MoS2 micro-arc oxidation layer preparation method is a frequency of 400Hz, a positive duty cycle of 30%, a negative duty cycle of 30%, a forward voltage of 350V, a negative voltage of 10V, and an oxidation time of 40min. Further, in the step three of this embodiment, the sealing liquid preparation method is to mix 1.5g / L KH507 with 10g / L organic solvent, stir for 48h for activation, and then add 10g / L potassium fluorozirconate, 3g / L nano titanium dioxide, and 3g / L triethanolamine ultrasonically oscillated for 0.5h. Furthermore, in step 3 of this embodiment, the sealing layer preparation method is to place the substrate with the TiO2 / MoS2 micro-arc oxidation layer in step 2 in the sealing liquid and soak it for 5 minutes, then place it in an oven at 160°C for 15 minutes, repeat 3 times and dry it for 30 minutes to obtain a substrate with a sealed TiO2 corrosion-resistant layer. Finally, in step 4 of this embodiment, the Ti / MoS2 layer preparation method is to place the substrate obtained in step 3 in a vacuum chamber of a vapor deposition device, maintain the vacuum degree at 1Pa, and then turn on the MoS2 target, the power supply used is a radio frequency power supply, and the sputtering power is set to 200W. Turn on the Ti target, the power supply used is a DC power supply, and the current size is set to 50A. The bias voltage is set to -200V, the duty cycle is 40%, the deposition time is 1h, and the Ti / MoS2 composite layer is plated.

[0046] In addition, the composite coating in this embodiment is composed of a micro-arc oxidation TiO2 / MoS2 layer, a TiO2 sealing layer and a vapor-deposited Ti / MoS2 layer, wherein the thickness of the TiO2 / MoS2 layer is 10 μm, the TiO2 sealing layer is 1 μm, the vapor-deposited Ti / MoS2 layer is 1 μm, and the atomic percentage of Ti in the Ti / MoS2 layer is 2%.

[0047] Embodiment 2: A method for preparing a composite coating and a composite coating, comprising the following steps: Step 1: Evenly disperse the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte.

[0048] Step 2: placing the clean titanium alloy substrate in the composite electrolyte of step 1 for micro-arc oxidation treatment to obtain a TiO2 / MoS2 micro-arc oxidation layer on the surface of the titanium alloy substrate.

[0049] Step three: immerse the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer in step two into a sealing liquid, and then dry it to obtain a substrate with a sealing TiO2 corrosion-resistant layer.

[0050] Step 4: Place the sample obtained in step 3 in the vacuum chamber of the vapor deposition equipment as the anode, use MoS2 target and Ti target as the cathode, and perform coating treatment in an argon atmosphere with a vacuum degree of 1 Pa to form a MoS2 / Ti layer on the surface to obtain a wear-resistant composite coating.

[0051] Wherein, in the step one of the embodiment, the activation method of MoS2 nano powder is: 20gMoS2 nano powder is immersed in a mixed solution of 0.08g sodium lauryl sulfate and 250g ethanol and stirred for 2h for activation treatment, and then dried and sieved to obtain the activated MoS2 nano powder. At the same time, in the step one of the embodiment, the composite electrolyte preparation method is to prepare 3g / L activated MoS2 nano powder, 12g / L sodium silicate, 0.8g / L sodium hypophosphite, 4g / L sodium tungstate, 2ml / L glycerol into electrolyte, continuously stirred for 1.5h, ultrasonic oscillation 1h, and the activated MoS2 nano powder is evenly distributed in the electrolyte. Secondly, in the step two of the embodiment, TiO2 / MoS2 micro-arc oxidation layer preparation method is frequency 600Hz, positive duty cycle 15%, negative duty cycle 15%, forward voltage 450V, negative voltage 30V, oxidation time 30min. Further, in step three of this embodiment, the sealing liquid preparation method is to mix 1g / L KH507 with 5g / L organic solvent, stir for 48h for activation, and then add 8g / L potassium fluorozirconate, 1.5g / L nano titanium dioxide, and 5g / L triethanolamine for ultrasonic vibration for 0.5h. Further, in step three of this embodiment, the sealing layer preparation method is to place the substrate with the TiO2 / MoS2 micro-arc oxidation layer in step two in the sealing liquid and soak for 5min, place it in an oven at 160℃ for 15min, repeat 4 times and then dry for 30min to obtain a substrate with a sealed TiO2 corrosion-resistant layer. Finally, in step four of this embodiment, the Ti / MoS2 layer preparation method is to place the substrate obtained in step three in the vacuum chamber of the vapor deposition equipment, maintain the vacuum degree at 1Pa, and then turn on the MoS2 target, the power supply used is a radio frequency power supply, and the sputtering power is set to 220W. Turn on the Ti target, the power supply used is a DC power supply, and the current size is set to 100A. The bias voltage was set to -300 V, the duty cycle was 50%, the deposition time was 2 h, and the Ti / MoS2 composite layer was plated.

[0052] Moreover, the composite coating in this embodiment is composed of a micro-arc oxidation TiO2 / MoS2 layer, a TiO2 sealing layer and a vapor-deposited Ti / MoS2 layer. The thickness of the TiO2 / MoS2 layer in the composite coating is 12 μm, the thickness of the TiO2 sealing layer is 1.2 μm, the thickness of the vapor-deposited Ti / MoS2 layer is 1.8 μm, and the atomic percentage of Ti in the Ti / MoS2 layer is 10%. At the same time, the electron microscope scanning image of the composite coating obtained based on this embodiment can be referred to Figure 2 shown.

[0053] Embodiment 3: A method for preparing a composite coating and a composite coating, comprising the following steps: Step 1: Evenly disperse the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte.

[0054] Step 2: placing the clean titanium alloy substrate in the composite electrolyte of step 1 for micro-arc oxidation treatment to obtain a TiO2 / MoS2 micro-arc oxidation layer on the surface of the titanium alloy substrate.

[0055] Step three: immerse the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer in step two into a sealing liquid, and then dry it to obtain a substrate with a sealing TiO2 corrosion-resistant layer.

[0056] Step 4: Place the sample obtained in step 3 in the vacuum chamber of the vapor deposition equipment as the anode, use MoS2 target and Ti target as the cathode, and perform coating treatment in an argon atmosphere with a vacuum degree of 1 Pa to form a MoS2 / Ti layer on the surface to obtain a wear-resistant composite coating.

[0057] Wherein, in the step one of the embodiment, the activation method of MoS2 nano powder is: 20gMoS2 nano powder is immersed in a mixed solution of 0.1g sodium lauryl sulfate and 300g ethanol and stirred for 2h for activation treatment, and then dried and sieved to obtain the activated MoS2 nano powder. At the same time, in the step one of the embodiment, the composite electrolyte preparation method is to prepare 5g / L activated MoS2 nano powder, 15g / L sodium silicate, 1g / L sodium hypophosphite, 5g / L sodium tungstate, 4ml / L glycerol into electrolyte, continuously stirred for 1.5h, ultrasonically vibrated for 1.5h, and the activated MoS2 nano powder is evenly distributed in the electrolyte. Secondly, in the example step two of the implementation, TiO2 / MoS2 micro-arc oxidation layer preparation method is frequency 600Hz, positive duty cycle 15%, negative duty cycle 15%, forward voltage 450V, negative voltage 30V, oxidation time 30min. Further, in step three of this embodiment, the sealing liquid preparation method is to mix 1g / L KH507 with 5g / L organic solvent, stir for 48h for activation, and then add 8g / L potassium fluorozirconate, 1.5g / L nano titanium dioxide, and 5g / L triethanolamine for ultrasonic vibration for 0.5h. Further, in step three of this embodiment, the sealing layer preparation method is to place the substrate with the TiO2 / MoS2 micro-arc oxidation layer in step two in the sealing liquid and soak for 5min, place it in an oven at 160℃ for 15min, repeat 4 times and then dry for 30min to obtain a substrate with a sealed TiO2 corrosion-resistant layer. Finally, in step four of this embodiment, the Ti / MoS2 layer preparation method is to place the substrate obtained in step three in the vacuum chamber of the vapor deposition equipment, keep the vacuum degree at 1Pa, and then turn on the MoS2 target, the power supply used is a radio frequency power supply, and the sputtering power is set to 250W. Turn on the Ti target, the power supply used is a DC power supply, and the current size is set to 100A. The bias voltage was set to -400 V, the duty cycle was 60%, the deposition time was 3 h, and the Ti / MoS2 composite layer was plated.

[0058] In addition, the composite coating in this embodiment is composed of a micro-arc oxidation TiO2 / MoS2 layer, a TiO2 sealing layer and a vapor-deposited Ti / MoS2 layer, wherein the thickness of the TiO2 / MoS2 layer is 13 μm, the thickness of the TiO2 sealing layer is 1.2 μm, the vapor-deposited Ti / MoS2 layer is 2 μm, and the atomic percentage of Ti in the Ti / MoS2 layer is 8%.

[0059] Embodiment 4: A method for preparing a composite coating and a composite coating, comprising the following steps: Step 1: Evenly disperse the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte.

[0060] Step 2: placing the clean titanium alloy substrate in the composite electrolyte of step 1 for micro-arc oxidation treatment to obtain a TiO2 / MoS2 micro-arc oxidation layer on the surface of the titanium alloy substrate.

[0061] Step three: immerse the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer in step two into a sealing liquid, and then dry it to obtain a substrate with a sealing TiO2 corrosion-resistant layer.

[0062] Step 4: Place the sample obtained in step 3 in the vacuum chamber of the vapor deposition equipment as the anode, use MoS2 target and Ti target as the cathode, and perform coating treatment in an argon atmosphere with a vacuum degree of 1 Pa to form a MoS2 / Ti layer on the surface to obtain a wear-resistant composite coating.

[0063] In step 1 of this embodiment, the activation method of MoS2 nanopowder is: immerse 10g MoS2 nanopowder in a mixture of 0.1g / L sodium dodecyl sulfate and 200g ethanol and stir for 2h for activation treatment, and then dry and sieve to obtain the activated MoS2 nanopowder.

[0064] Wherein, in the step one of this embodiment, the composite electrolyte preparation method is to prepare 5g / L activated MoS2 nanopowder, 15g / L sodium silicate, 1g / L sodium hypophosphite, 5g / L sodium tungstate, and 8ml / L glycerol into an electrolyte, continuously stirred for 2h, ultrasonically oscillated for 1.5h, and the activated MoS2 nanopowder is evenly distributed in the electrolyte. Meanwhile, in the step two of this embodiment, the TiO2 / MoS2 micro-arc oxidation layer preparation method is a frequency of 800Hz, a positive duty cycle of 5%, a negative duty cycle of 5%, a forward voltage of 500V, a negative voltage of 50V, and an oxidation time of 20min. Secondly, in the step three of this embodiment, the sealing liquid preparation method is to mix 0.5g / L KH507 with 2g / L organic solvent, stir for 36h for activation, and then add 5g / L potassium fluorozirconate, 1g / L nano titanium dioxide, and 1g / L triethanolamine ultrasonically oscillate for 0.5h. Further, in step three of this embodiment, the sealing layer preparation method is to place the substrate with the TiO2 / MoS2 micro-arc oxidation layer in step two in the sealing liquid and soak for 5 minutes, then place it in an oven at 160°C for 15 minutes, repeat 5 times and then dry for 30 minutes to obtain a substrate with a sealed TiO2 corrosion-resistant layer. Finally, in step four of this embodiment, the preparation method of the Ti / MoS2 layer is to place the substrate obtained in step three in a vacuum chamber of a vapor deposition device, maintain the vacuum degree at 1Pa, and then turn on the MoS2 target, the power supply used is a radio frequency power supply, and the sputtering power is set to 250W. Turn on the Ti target, the power supply used is a DC power supply, and the current size is set to 100A. The bias voltage is set to -400V, the duty cycle is 60%, the deposition time is 3h, and the Ti / MoS2 composite layer is plated.

[0065] Moreover, the composite coating in this embodiment is composed of a micro-arc oxidation TiO2 / MoS2 layer, a TiO2 sealing layer and a vapor-deposited Ti / MoS2 layer, wherein the thickness of the TiO2 / MoS2 layer is 15 μm, the TiO2 sealing layer is 1 μm, the vapor-deposited Ti / MoS2 layer is 2 μm, and the atomic percentage of Ti in the Ti / MoS2 layer is 8%.

[0066] Comparative Example 1: A method for preparing a wear-resistant composite coating on a titanium alloy surface may include the following steps: Step 1: Evenly disperse the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte.

[0067] Step 2: placing the clean titanium alloy substrate in the composite electrolyte of step 1 for micro-arc oxidation treatment to obtain a TiO2 / MoS2 micro-arc oxidation layer on the surface of the titanium alloy substrate.

[0068] Wherein, in step 1 of this embodiment, the activation method of MoS2 nano powder is: 20gMoS2 nano powder is immersed in a mixed solution of 0.08g sodium lauryl sulfate and 250g ethanol and stirred for 2h for activation treatment, and then dried and sieved to obtain the activated MoS2 nano powder. At the same time, in step 1 of this embodiment, the composite electrolyte preparation method is to prepare 3g / L activated MoS2 nano powder, 12g / L sodium silicate, 0.8g / L sodium hypophosphite, 4g / L sodium tungstate, and 2ml / L glycerol into an electrolyte, continuously stirred for 1.5h, ultrasonically vibrated for 1h, and the activated MoS2 nano powder was evenly distributed in the electrolyte.

[0069] Moreover, the coating obtained in this comparative example is a micro-arc oxidation TiO2 / MoS2 layer. At the same time, the electron microscope scanning image of the micro-arc oxidation layer obtained based on this comparative example can be referred to Figure 3 shown.

[0070] Figure 4 The morphology obtained after hot salt corrosion on a titanium alloy substrate is schematically shown; Figure 5 The morphology obtained after hot salt corrosion on the surface of the composite coating obtained in Example 2 is schematically shown; Figure 6 The morphology obtained after hot salt corrosion on the surface of the micro-arc oxidation layer obtained in Comparative Example 1 is schematically shown. Figure 4-Figure 6 It can be seen that, on the one hand, for the composite coating obtained by applying the above-mentioned Example 2 of the present disclosure, compared with the titanium alloy substrate and the micro-arc oxidation layer, the coating preparation scheme of Example 2 can significantly improve the corrosion resistance of the titanium alloy. Further, Table 1 shows the friction coefficient and wear rate of the titanium alloy surface coating in the titanium alloy substrate, Example 2 of the present invention and the comparative example. It can be seen that compared with the titanium alloy substrate, the friction reduction and wear resistance of the composite coating obtained in Example 2 of the present disclosure are significantly improved. Compared with the comparative example, the wear resistance of the composite coating obtained in Example 2 of the present disclosure is similar, and the friction reduction is significantly improved.

[0071] Table 1

[0072] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.

[0073] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.

[0074] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.

Claims

1. A method for preparing a composite coating, characterized in that: include: Step 1: Evenly dispersing the activated MoS2 nanopowder in the electrolyte to obtain a composite electrolyte; Step 2: placing the titanium alloy substrate in the composite electrolyte for micro-arc oxidation treatment to generate a micro-arc oxidation layer with TiO2 / MoS2 on the surface of the titanium alloy substrate; Step 3: immersing the titanium alloy substrate with the TiO2 / MoS2 micro-arc oxidation layer into a sealing liquid, followed by drying to obtain a substrate with a sealed TiO2 corrosion-resistant layer; Step 4: Place the substrate with the sealed TiO2 corrosion-resistant layer in the vacuum chamber of the vapor deposition equipment as the anode, use the MoS2 target and the Ti target as the cathode, and perform coating treatment in an argon atmosphere with a vacuum degree of 1 Pa to form a wear-resistant composite coating on the surface of the substrate with the sealed TiO2 corrosion-resistant layer.

2. The method for preparing the composite coating according to claim 1, characterized in that: The activated MoS2 nanopowder used in the preparation process of the composite electrolyte is obtained in the following way: 10-20g of MoS2 nanopowder is immersed in a mixture of 0.05-0.1g of sodium dodecyl sulfate and 200-300g of ethanol and stirred for 2h for activation treatment to obtain an activated mixed solution, and the activated mixed solution is dried and sieved to obtain activated MoS2 nanopowder.

3. The method for preparing the composite coating according to claim 1, characterized in that: The preparation process of the composite electrolyte is obtained by the following method: 1-5g / L activated MoS2 nanopowder, 10-15g / L sodium silicate, 0.5-1g / L sodium hypophosphite, 2-5g / L sodium tungstate, and 2-8ml / L glycerol are prepared into an electrolyte, which is continuously stirred for 1-2h and ultrasonically vibrated for 0.5-1.5h to evenly distribute the activated MoS2 nanopowder in the electrolyte.

4. The method for preparing the composite coating according to claim 1, characterized in that: In the preparation process of the micro-arc oxidation layer with TiO2 / MoS2, the frequency used in the micro-arc oxidation process is 400-800Hz, the forward duty cycle is 5-30%, the negative duty cycle is 5%-30%, the forward voltage is 350-500V, the negative voltage is 10-50V, and the oxidation time is 20-40min.

5. The method for preparing the composite coating according to claim 1, characterized in that: The sealing liquid is prepared by the following method: 1) Mixing 0.5-1.5 g / L of silane coupling agent with 2-10 g / L of organic solvent to obtain a solvent mixing result; 2) Stirring the solvent mixture for 36-48 hours to activate the solvent mixture to obtain a solvent activation result; 3) Add 5-10 g / L potassium fluorozirconate, 1-3 g / L nano titanium dioxide and 1-5 g / L triethanolamine to the solvent activation result and ultrasonically vibrate for 0.5 h to obtain the sealing liquid.

6. The method for preparing the composite coating according to claim 1, characterized in that: The substrate with a sealed TiO2 corrosion-resistant layer is prepared in the following manner: a titanium alloy substrate with a TiO2 / MoS2 micro-arc oxidation layer is placed in a sealing liquid and immersed for 5-10 minutes, and the immersed titanium alloy substrate is placed in an oven and baked at 160°C for 15 minutes, and then the baking is repeated 3-5 times and then dried again for 30 minutes to obtain a substrate with a sealed TiO2 corrosion-resistant layer.

7. The method for preparing the composite coating according to claim 1, characterized in that: The composite coating is prepared by the following method: 1) placing a substrate with a sealed TiO2 corrosion-resistant layer in a vacuum chamber of a vapor deposition device and maintaining the vacuum degree at 1 Pa; 2) turning on the MoS2 target, using a radio frequency power supply as the power source, and setting the sputtering power of the radio frequency power supply to 200-250W; 3) turning on the Ti target, using a direct current power supply as the power source, setting the current of the direct current power supply to 50-100A, setting the bias voltage to -200V~-400V, the duty cycle to 40%-60%, and the deposition time to 1-3h, so as to plate the composite coating on the surface of the substrate with the sealed TiO2 corrosion-resistant layer.

8. A composite coating obtained by the method for preparing a composite coating according to any one of claims 1 to 7, characterized in that: The composite coating comprises a micro-arc oxidation TiO2 / MoS2 layer, a TiO2 pore sealing layer and a vapor-deposited Ti / MoS2 layer.

9. The composite coating according to claim 8, characterized in that: The thickness of the micro-arc oxidation TiO2 / MoS2 layer is 10-15 μm; the thickness of the TiO2 sealing layer is 1-1.5 μm; and the thickness of the vapor deposited Ti / MoS2 layer is 1-3 μm.

10. The composite coating according to claim 8, characterized in that: The atomic percentage of Ti in the vapor deposited Ti / MoS2 layer is 2%-10%.

Citation Information

Patent Citations

  • Preparation method of molybdenum disulfide base lubricating wear-resistant composite film

    CN101906614A

  • Multi-arc ion-plating-aluminum based micro-arc oxidation ceramic coating on titanium alloy surface and preparation method of multi-arc ion-plating-aluminum based micro-arc oxidation ceramic coating

    CN106702329A

  • Coated metal alloy substrate and method of making same

    CN114929938A

  • Molybdenum disulfide-aluminum self-lubricating coating suitable for titanium alloy and application of molybdenum disulfide-aluminum self-lubricating coating

    CN115491643A

  • Wear-resistant and corrosion-resistant coating as well as preparation method and application thereof

    CN116657101A